Pengaruh Reproduksi Ruang terhadap Perubahan Sosial dan Ekonomi Masyarakat Setempat di Kelurahan Samata Kabupaten Gowa - Aulia, Nur Rahmi; AS, Nur Syam; Surur, Fadhil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
AbstractSamata Urban Village is located in Gowa Regency, the emergence of new areas in the Samata Urban Village replaces the land that was originally occupied by the local community to be transformed into an elite and luxurious area, both that occurred in the city center and in the periphery. The process of rehabilitation and urban renewal is what is referred to as gentrification which in the end urban spaces are utilized by those with high income into real estate. This study aims to identify general condition, to determine the reproduction of space and the impact to social and economic. The analytical method used is superimpose analysis and descriptive analysis. Based on the analysis it was found that with the reproduction of space for the construction of economic and residential facilities that have a high value impact, so many people sell their land. Changes in social and economic conditions according to the correlation analysis of the influence of the development of the Village Samata gave a large influence on population growth with a correlation value of 0.98 with a very strong influence and job development with a correlation value of 0.80 with a very strong influence. So the influence of spatial reproduction in Samata Village has a big impact on the development of physical space in the Samata Village.